Integrated Genomic and Transcriptomic Analyses of Diffuse Large B-Cell Lymphoma With Multiple Abnormal Immunologic Markers - Sheng, Lingshuang; Fu, Di; Cao, Yiwen; Huo, Yujia; Wang, Shuo; Shen, Rong; Xu, Pengpeng; Cheng, Shu; Wang, Li; Zhao, Weili (Frontiers in Oncology, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is a highly aggressive subtype of lymphoma and related to autoimmune diseases (AIDs). Primary B-cell receptor-mediated AIDs are associated with poor clinical outcome of DLBCL. To further determine the role of immunological alterations on disease progression, our study integrated genomic and transcriptomic analyses on DLBCL with multiple abnormal immunologic markers. Methods: Clinical data of 1,792 patients with newly diagnosed DLBCL were collected, with DNA- and RNA-sequencing conducted for 164 and 127 patients, respectively. Frequent gene mutations and involved dysregulated pathways, along with gene expression pattern and tumor microenvironment alternations, were analyzed and compared based on the immune status of the patients. Results: DLBCL with multiple abnormal immunologic markers demonstrated a variety of characteristics including elevated serum lactic dehydrogenase level, inferior prognosis, dysregulated cell cycle and immune response, as well as activated oxidative phosphorylation pathway and increased Th1/Th2 and Th17/Treg ratios, which were highly similar as those occur in AIDs. Conclusions: We piloted the description of the clinical and genetic features of DLBCL with multiple abnormal immunologic markers, illustrated possible mechanisms of disease progression, and provided clinical rationale of mechanism-based targeted therapy in this subset of DLBCL.